Fear and What Follows : The Violent Education of a Christian Racist, A Memoir - Parrish, Tim (Book collections on Project MUSE., 2013)
This book is an unflinching account of the author's spiral into racist violence during the latter years of desegregation in 1960s and 1970s Baton Rouge. The narrative of the Tim Parrish's descent into fear and irrational behavior begins with bigotry and apocalyptic thinking in his Southern Baptist church. Living a life upon this volatile foundation of prejudice and apprehension, he feels destabilized by his brother going to Vietnam, his own puberty and restlessness, serious family illness, and economic uncertainty. Then a near-fatal street fight and subsequent stalking by an older sociopath fracture what security is left, leaving him terrified and seemingly helpless. Parrish comes to believe that he can only be safe by allying himself with brute force. This brute influence is a vicious, charismatic racist. Under this bigot's terrible sway, Parrish turns to violence in the street and at school. He is even conflicted about whether he will help commit murder in order to avenge a friend. At seventeen, he must reckon with all of this as his parents and neighbors grow increasingly afraid that they are "losing" their neighborhood to African Americans. This is an unparalleled story of the complex roots of southern, urban, working-class racism and white flight, as well as a story of family, love, and the possibility of redemption.